DEVELOPMENT OF MATHEMATICS LEARNING USING BATAK CULTURE- BASED MEDIA IN INDONESIA - Panjaitan, Dedy Juliandri; Firmansyah, Firmansyah; Sapta, Andy; Aprilia, Rima; Siregar, Annisa Fadhillah Putri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to develop Batak culture-based domino card learning media to enhance students’ interest and academic achievement in three challenging mathematics topics: trigonometry, integer operations, and logarithms. The research explores how local cultural values, specifically the Batak kinship philosophy Dalihan Na Tolu, can be meaningfully integrated into mathematics instruction. Employing a design-based research (DBR) approach, the study was conducted in seven schools across North Sumatra Province, Indonesia. The development process encompassed media design, expert validation, classroom implementation, and iterative refinement. Instruments utilized included teacher interviews, classroom observations, student questionnaires, and achievement tests. The findings indicate that integrating Dalihan Na Tolu values into game- based learning media provides culturally resonant analogies that enhance students’ understanding of abstract mathematical concepts. In trigonometry, visual and cultural representations helped students distinguish among triangle elements and apply ratio concepts in problem-solving. In the context of integer operations, the domino gameplay facilitated students’ comprehension of signed numbers through contextual scenarios such as altitude and temperature changes. For logarithms, visual simulations and matching exercises supported students in grasping the inverse relationship between exponents and logarithmic expressions. The application of culturally contextualized game-based media not only improved students’ comprehension across all three mathematical topics but also significantly increased their engagement and interest in learning. These findings suggest that incorporating local cultural values into instructional tools can offer an innovative and effective model for advancing mathematics education, particularly in culturally diverse contexts.